Characteristic of Microplastic on Coral Reef Sediment and Sea Urchin (Diadema sp.) in Tidung Island, Jakarta Bay, Indonesia - Sulistiowati, Sulistiowati; Zamani, Neviaty Putri; Bengen, Dietriech Geofrfey; Lim, Cheng Ling; Cordova, Muhammad Reza (Marine Science Department Diponegoro University, 2023)
Microplastics are recognized as common contaminants of coral ecosystem in Tidung Island, affecting both sediment and sea urchins residing in this environment. Therefore, this study aimed to determine the characteristics of microplastics found in sediment, the mouth, and the digestive system of sea urchins (Diadema sp.), assessing the relationship between coral cover percentage and microplastic type and size, and the transfer of microplastics from sediment to sea urchins. Sampling was conducted twice, namely in October 2021 and October 2022. Microplastics in sediments were extracted using ZnCl2. The destruction process of sea urchins used 30% H2O2 and FeSO4.7H2O, while the microplastics were identified with Attenuated Total Reflection Fourier Transform Infrared Spectroscopy (ATR-FTIR). The results showed that the microplastics found in the sediments and sea urchins were similar in terms of shape, color, size, and plastic polymers. The forms of microplastics found in this study were fibre, fragment, and foam with fibre predominance, based on the results obtained. The size of microplastics found in sediments and sea urchins was dominated by sizes >1000 µm. Fibres were found in hard coral (HC) and dead coral (DC) conditions while fragments and foams were present in turf algae (TA), sponge (SP), and soft coral (SC) conditions. The microplastics found in sea urchins originate in part from sediments because they have similar characteristics. Sea urchins ingested microplastics from sediment, particularly those grown by algae as a food source. The increase in the number of microplastics found in sediment could potentially result in higher abundance in the biota.